2009
DOI: 10.1002/hyp.7191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ENSO and the Indian Ocean Dipole on the north‐east monsoon rainfall of Tamil Nadu State in India

Abstract: Abstract:Tamil Nadu State in south-eastern India receives most of its rainfall from October through December, a phenomenon known as north-east monsoon rainfall (NEMR). Tamil Nadu's south-west monsoon rainfall (SWMR), received between June and September, correlates positively with the Southern Oscillation Index (SOI), whereas NEMR correlates negatively. We undertook a study to investigate the relationship between global teleconnection indicators, namely the El Niño-Southern Oscillation (ENSO) and the Indian Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…A good deal of research has been conducted at the scale of the Indian subcontinent, some of it reviewed here, and it is vital to place Sri Lanka in its regional context. For example, in relation to the NEM, authors in [10] found similar results in Tamil Nadu, Southeast India, to those presented here in terms of ENSO controls on rainfall totals. With regard to the SWM, the findings of [32] show that being able to place Sri Lanka in its wider regional context could be very worthwhile since this could aid forecasting of the onset of the monsoonal circulation and associated precipitation further north in the Indian subcontinent and hopefully enable monsoon failures to be better anticipated.…”
Section: Physical Mechanisms Of Enso Teleconnectionssupporting
confidence: 68%
“…A good deal of research has been conducted at the scale of the Indian subcontinent, some of it reviewed here, and it is vital to place Sri Lanka in its regional context. For example, in relation to the NEM, authors in [10] found similar results in Tamil Nadu, Southeast India, to those presented here in terms of ENSO controls on rainfall totals. With regard to the SWM, the findings of [32] show that being able to place Sri Lanka in its wider regional context could be very worthwhile since this could aid forecasting of the onset of the monsoonal circulation and associated precipitation further north in the Indian subcontinent and hopefully enable monsoon failures to be better anticipated.…”
Section: Physical Mechanisms Of Enso Teleconnectionssupporting
confidence: 68%
“…Although the SO has severe impacts on the tropic latitudes, in particular, for countries that are affected by monsoons (such as India, Indonesia, Africa and Australia), and its influence has been detected in different locations all over the globe (Bhuvaneswari et al ., ). Due to its global effect, a considerable amount of research works have been conducted to explore the relationship of hydrological surface variables in association with SO (e.g., Kahya and Dracup, ; Kahya and Dracup, ; Kalayci et al ., ; Kumar et al ., ; Geethalakshmi et al ., ; Ward et al ., ).…”
Section: Large‐scale Atmospheric Oscillationsmentioning
confidence: 99%
“…Many studies have shown that the variability of rainfall in Asia and Southeast Asia has been affected by the El Niño-Southern Oscillation (ENSO). ENSO is a naturally occurring phenomenon that involves fluctuation of ocean temperatures in the equatorial Pacific (Yamagata et al, 2004;Geethalakshmi et al, 2009;Timo and Matti, 2013). However, the influence of climate variability on oceans and the corresponding impact on regional rainfall variability is unclear.…”
Section: Introductionmentioning
confidence: 99%